Two new recorded species of the family Leptonchidae (Nematoda: Dorylaimida) for Vietnam’s fauna from Cuc Phuong national park - Anh Duong, Nguyen Thi; Thanh Tam, Vu Thi; Peña-Santiago, Reyes (Academia Journal of Biology, 2012)
Proleptonchus aestivus and Tyleptus projectus from Cuc Phuong natural forest are described and illustrated for the first time in Vietnam. Proleptonchus aestivus species is characterized by its body 1.14-1.21 mm long; lip region cap-like with lips amalgamated and papillae little protruding; odontostyle very slender and odontophore rod-like, arcuate; female genital system mono-prodelphic; tail short and rounded, hemispheroid. Tyleptus projectus species is characterized by its body 0.79-0.95 mm long; lip region set off by marked depression or weak constriction; six lips conspicuous projecting liplets around the oral opening; odontostyle small but robust, odontophore rod-like; female genital system mono-opisthodelphic, male genital system diorchic, with opposite testes. Tail short and rounded, to hemispheroid.